Conditioning factors on regional European clubs - a distributional approach - Toni Mora (European Regional Science Association (ERSA), 2005)
Growth literature has considered the existence of groups of economies which have been termed convergence clubs. Literature confirms their existence for European regional case. This paper has focused on how conditioning factors are influencing European regional GDPpc distribution. The estimation of conditioned stochastic kernels is the optimum methodology to consider whole distribution or partial conditionings
Keywords: 330